Analisis Sistem Pengendalian Intern Penerimaan Dan Pengeluaran Kas Pada PT. Balindo Sejahtera Bersama - Ni Made Safitri; Ni Putu Ayu Kusumawati Novitayanti (UNHI Press, 2026)
Internal Control is a process carried out under the mandate of the board of directors or management within an organization, aimed at protecting the company's assets and ensuring compliance with applicable laws and regulations. This research was conducted at PT Balindo Sejahtera Bersama, a company engaged in the property agency sector. The purpose of this research is to determine the implementation of the internal control system for cash receipts and disbursements at PT Balindo Sejahtera Bersama. The method used in this research is the comparative analysis method, which involves analyzing the conditions of the company being studied and comparing them with existing theories to draw conclusions on whether the internal cash control system in the research object aligns with the theory or not. The data collection techniques used are through observation, interviews, documentation, and literature study. The results of this study indicate that PT Balindo Sejahtera Bersama has not yet implemented an internal control system effectively and is not fully in accordance with existing theories, as there are still elements of internal control within the company that have not been fully executed.